2010
DOI: 10.1093/jac/dkq017
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid use for treatment of multidrug-resistant and extensively drug-resistant tuberculosis, New York City, 2000-06

Abstract: The majority of MDR TB patients on linezolid had favourable treatment outcomes, although treatment was complicated by adverse events that required extensive clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 16 publications
0
77
0
5
Order By: Relevance
“…18,19 Study characteristics for the 11 included studies are summarised in Table 1. [10][11][12][20][21][22][23][24][25][26][27] A total of 218 patients received linezolid, of whom 148 had evaluable outcomes; the remainder were reported to have been still receiving treatment at the time of publication. All patients were adults, and all were infected with MDR-TB, of whom at least 62 (28%) were infected with XDR-TB strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Study characteristics for the 11 included studies are summarised in Table 1. [10][11][12][20][21][22][23][24][25][26][27] A total of 218 patients received linezolid, of whom 148 had evaluable outcomes; the remainder were reported to have been still receiving treatment at the time of publication. All patients were adults, and all were infected with MDR-TB, of whom at least 62 (28%) were infected with XDR-TB strains.…”
Section: Resultsmentioning
confidence: 99%
“…Linezolid has demonstrated high in vitro antibacterial activity against Mycobacterium tuberculosis, 8,9 and has been used to treat complicated cases of resistant TB in several programmes. [10][11][12] Given that patients with refractory and/or XDR-TB have few treatment options, linezolid may well be a useful addition to the armamentarium. However, linezolid is a toxic drug with significant side effects, including severe neuropathies and haematological adverse events.…”
Section: Drug-resistant Tuberculosis (Dr-tb) Ismentioning
confidence: 99%
“…Published clinical trials have shown that linezolid plays an important role as part of an optimized MDR-or XDR-TB regimen (16,17). In these studies, linezolid was used in combination with other anti-TB drugs; accordingly, its antibacterial activity was not directly measured.…”
mentioning
confidence: 99%
“…6,7 Furthermore, oxazolidinone class antibiotics show good activity against multidrug resistance Mycobacterium tuberculosis infections which is one of the most threatening and wide spreading infectious disease. [8][9][10] Linezolid is known to inhibit bacterial protein synthesis by binding to 50S ribosomal subunit at the translation step and prevent the formation of 70S complex, and the binding mode was confirmed by X-ray crystallography.…”
Section: Introductionmentioning
confidence: 91%